Steady State and Transient Analysis of Grid Connected Doubly Fed Induction Generator Under Different Operating Conditions - Sukhwinder Singh Dhillon; Jagdeep Singh Lather; Sanjay Marwaha (International Journal of Applied Power Engineering (IJAPE), 2017)
This paper present steady state and dynamic (Transient) models of the doubly fed induction generator connected to grid. The steady state model of the DFIAG (doubly fed asynchronous induction generator) has been constructed by referring all the rotor quantities to stator side. With the help of MATLAB programming simulation results are obtained to depict the steady state response of electromechanical torque, rotor speed, stator and rotor currents, stator and rotor fluxes, active and reactive drawn and delivered by Doubly Fed Asynchronous Induction Machine (DFAIM) as it is operating in two modes i.e. generator and motor. The mathematical steady state and transient model of the DFIAM is constructed for three basic reference frames such as rotor, stator and synchronously revolving reference frame using first order deferential equations. The effect of unsaturated and saturated resultant flux on the mutual inductance is also taken into account to deeply understand the dynamic response of the machine. The steady state and dynamic response of the DFAIG are compared for different rotor voltage magnitudes. Also, the effect of variations in mechanical input torque, stator voltage variations are simulated to predict the stator and rotor currents, active and reactive power, electromagnetic torque and rotor speed variations.